BUILDING STUDENTS' SKILLS IN READING POETRY TEXTS WITH CREATIVITY AND INTEREST - Telaumbanua, Nening Rosline; Ndruru, Mastawati; Laowo, Darni Marsellin; Buulolo, Festina (Primary Education Journals (Jurnal Ke-SD-An), 2024)
The aim of this research is to arouse students' interest in reading poetry through a poetry musicalization approach. The service team conducted a situation analysis with partners and found that students' interest in reading poetry was low due to a lack of understanding and appreciation of poetry and a lack of student creativity in representing poetry. Creativity can help students develop critical and creative thinking skills, solve problems, and innovate in various fields. The musicalization of poetry approach was chosen as the method in this activity because it can increase appreciation and understanding of literary works, especially poetry. Musicalization of poetry can make poetry more interesting and easier for students to understand and improve students' language and artistic skills. This method is effective for increasing appreciation of poetry and helping students to develop their creative abilities.